Problems in fiscal and monetary policy : a case study of Nepal - Pant, Yadav Prasad (London, C. Hurst, 1970)
The main object of this book focused on the basic problems of mobilizing adequate and real financial resources, for rapid economic development in a country like Nepal, which was almost a sealed letter to the outside world until 1950. It examines the economic underdevelopment of Nepal from the fiscal and monetary perspective and proffers solutions to it.
Includes index
Bibliography: p. 195-198.
usc 16/6/17
Loans
Keywords: Monetary policy; Fiscal policy; Nepal